1990
DOI: 10.1007/bf01063555
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic assessment of apparent facilitation by albumin of cellular uptake of unbound ligands

Abstract: Previous studies of the effect of albumin on initial uptake of ligands by isolated cell suspensions or cultures found that the apparent uptake for unbound ligand appeared larger in the presence of binding to the albumin than when albumin was absent. Furthermore, when ligand and albumin were increased in a fixed molar ratio, uptake appeared to be competitively inhibited by the excess albumin. We examined the kinetics underlying this apparent facilitation phenomenon by incorporating unbound fraction of ligand in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The model also assumed that the uptake and excretion of TC are the main rate determinants for TC transport and that intracellular trafficking by intracellular diffusion of free and bound TC is sufficiently rapid so that intracellular binding and diffusion are not rate limiting. It is possible that the known TC protein binding facilitated transport (Blitzer & Lyons, 1985) may result in apparent 'well-stirred' model behavior as noted by Morgan et al (1990). The poorer fitting of [ 3 H]TC data with both the slow diffusion/ bound and the slow binding models compared to the 'wellstirred' hepatobiliary TC transport model was seen as supportive of the assumption that the intrahepatocellular transport processes were not rate limiting for TC.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The model also assumed that the uptake and excretion of TC are the main rate determinants for TC transport and that intracellular trafficking by intracellular diffusion of free and bound TC is sufficiently rapid so that intracellular binding and diffusion are not rate limiting. It is possible that the known TC protein binding facilitated transport (Blitzer & Lyons, 1985) may result in apparent 'well-stirred' model behavior as noted by Morgan et al (1990). The poorer fitting of [ 3 H]TC data with both the slow diffusion/ bound and the slow binding models compared to the 'wellstirred' hepatobiliary TC transport model was seen as supportive of the assumption that the intrahepatocellular transport processes were not rate limiting for TC.…”
Section: Discussionmentioning
confidence: 90%
“…The model also assumed that the uptake and excretion of TC are the main rate determinants for TC transport and that intracellular trafficking by intracellular diffusion of free and bound TC is sufficiently rapid so that intracellular binding and diffusion are not rate limiting. It is possible that the known TC protein binding facilitated transport (Blitzer & Lyons, 1985) may result in apparent ‘well‐stirred’ model behavior as noted by Morgan et al . (1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, direct anatomical measurements of the size of the unstirred water layer in the intact sinusoid have yet to be determined. Morgan et al(1990) suggested that the kinetic analysis used by others was inappropriate. They used a kinetic model which incorporated the unbound fraction of ligand into the general model for diffusion between two compartments and showed that the apparent rateconstant for unbound ligand concentration increased with albumin concentration, although the uptake clearance of unbound ligand remained constant.…”
mentioning
confidence: 99%
“…There is abundant discussion and debate on this point, nicely reviewed by Weisiger 42 and extended by Schwab and Goresky. 28 Expressing a viewpoint opposite to ours, Morgan et al 21 show that the flux of ligand across an inert membrane between two compartments (mixing chambers without diffusion gradients) was constant over a wide range of total ligand concentrations at constant ligand/albumin ratio, and that the fraction of ligand permeating diminishes as the albumin concentration is increased. Our present model will give these results by setting the diffusion coefficients and k d1 to high values.…”
mentioning
confidence: 99%